1984
DOI: 10.1177/030098588402100413
|View full text |Cite
|
Sign up to set email alerts
|

Diarrhea Associated with Cryptosporidium spp in Juvenile Macaques

Abstract: Cryptosporidia are coccidian parasites of the suborder Eimeriorina. They have been found inhabiting the mucosa of the stomach, small and large intestine, gall bladder and bile ducts, pancreatic ducts and respiratory tract of a wide variety of animal species. A clinical syndrome of watery diarrhea, often severe and sometimes fatal, has been reported in guinea pigs, (bovine) calves, pigs, Arabian foals, rhesus macaques, and man.'-'The cases reported here are from three species of macaques-two Macaca mulatta (I a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…Reports of intestinal, hepatopancreatic, and pulmonary cryptosporidiosis in immunocompetent, infant, rhesus, and other macaques have been attributed to an organism with oocysts indistinguishable from those of C. parvum (59,171,349). Miller et al (220) reported 81 cases of acute cryptosporidiosis among 152 infant primates, predominantly Macaca nemestrina, housed in the nursery unit of the Washington Regional Primate Research Center.…”
Section: Nonhuman Primatesmentioning
confidence: 99%
“…Reports of intestinal, hepatopancreatic, and pulmonary cryptosporidiosis in immunocompetent, infant, rhesus, and other macaques have been attributed to an organism with oocysts indistinguishable from those of C. parvum (59,171,349). Miller et al (220) reported 81 cases of acute cryptosporidiosis among 152 infant primates, predominantly Macaca nemestrina, housed in the nursery unit of the Washington Regional Primate Research Center.…”
Section: Nonhuman Primatesmentioning
confidence: 99%
“…hominis in animals housed at the same place and in none of them it was found any organism related to this parasite 36 .…”
Section: Table 2 -Blastocystis Hominis-like Infections In Monkeysmentioning
confidence: 92%
“…This makes nonhuman primates an excellent model for studying agents of diarrheal infection. The IPRL has played an important role in studying two enteric pathogens (Campylobacter and Cryptosporidium) which cause diarrheal illness in both humans and nonhuman primates [Wilson et al, 1984; Navin & Juranek, 1984]…”
Section: Research In Reproductive and Developmental Sciences At The Iprlmentioning
confidence: 99%